2019
DOI: 10.1186/s12885-019-6206-z
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of iASPP is required for autophagy in response to oxidative stress in choriocarcinoma

Abstract: Background Gestational trophoblastic disease (GTD) is a heterogeneous group of diseases developed from trophoblasts. ASPP (Ankyrin-repeat, SH3-domain and proline-rich region containing protein) family proteins, ASPP1 and ASPP2, have been reported to be dysregulated in GTD. They modulate p53 activities and are responsible for multiple cellular processes. Nevertheless, the functional role of the ASPP family inhibitory member, iASPP, is not well characterized in GTD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…3A). Among them, FOXA1, PLAT, CD44, FGF5, DIO2 and other genes are upregulated, whereas PLCB1, SETBP1, EHD3, ZNF423, PHGDH and other genes are downregulated in multiple senescence systems(Chan et al, 2019; Cho et al, 2019; Galanos et al, 2016; Hari et al, 2019; Hernandez-Segura et al, 2017; Komseli et al, 2018; Lau, Porciuncula, Yu, Iwakura, & David, 2019; Leveque et al, 2019; Q. Li et al, 2013; Limbad et al, 2020; Lowe & Raj, 2014; Nagano et al, 2016; Pan et al, 2019; Pantazi et al, 2019; Suwan et al, 2009; Wu, Pepowski, Takahashi, & Kron, 2019; Zhou et al, 2010), as are consistent with our results.…”
Section: Resultssupporting
confidence: 92%
“…3A). Among them, FOXA1, PLAT, CD44, FGF5, DIO2 and other genes are upregulated, whereas PLCB1, SETBP1, EHD3, ZNF423, PHGDH and other genes are downregulated in multiple senescence systems(Chan et al, 2019; Cho et al, 2019; Galanos et al, 2016; Hari et al, 2019; Hernandez-Segura et al, 2017; Komseli et al, 2018; Lau, Porciuncula, Yu, Iwakura, & David, 2019; Leveque et al, 2019; Q. Li et al, 2013; Limbad et al, 2020; Lowe & Raj, 2014; Nagano et al, 2016; Pan et al, 2019; Pantazi et al, 2019; Suwan et al, 2009; Wu, Pepowski, Takahashi, & Kron, 2019; Zhou et al, 2010), as are consistent with our results.…”
Section: Resultssupporting
confidence: 92%
“…S3 B ). This attracted our attention because iASPP has been shown to be overexpressed in multiple cancers, including COAD ( 35 , 40 42 ), and our data also revealed that iASPP was increased in colon cancer tissues compared with matched adjacent normal controls ( Fig. 3 E ).…”
Section: Resultsmentioning
confidence: 68%
“…Downregulation of a member of apoptosis-stimulating proteins of p53 (ASPPs), ASPP1 was demonstrated in GTD and lower ASPP1 was also shown in progression to GTN which may explain the pathogenesis through decreased apoptosis [23]. Another study revealed the overexpression of ASPP family inhibitory member iASPP, with a progressive increase from hydatidiform mole to choriocarcinoma [24]. Another study showed that a molecule DJ-1 as a regulator of Phosphatase and TENsin homolog deleted on chromosome 10 (PTEN), which is a frequently mutated tumor suppressor gene in carcinogenesis may play a role in apoptotic activity regulation of GTD in relation to PTEN and p53 [25].…”
Section: Discussionmentioning
confidence: 99%